Pituitary adenoma: a literature review - Sidaraitė , A.; Glebauskienė , B.; Liutkevičienė , R. (Neurologijos seminarai, 2018)
Pituitary adenoma is one of the most common intracranial tumors which cause neurological and/or hormonal symptoms. Nevertheless, its pathogenesis remains unclear – familial cases and syndromes are known better than sporadic cases. Many studies are carried out to find somatic or epigenetic changes in cases with sporadic adenomas which could affect its pathogenesis. The discovery of these changes may lead to biomarkers invention which could be used to diagnose pituitary adenomas, especially atypical and aggressive types in early stages. In this article, we review the classification of these tumors, pathogenesis of familial and sporadic pituitary adenomas, common principles of its diagnostics and treatment.
Keywords: pituitary adenoma; epigenetics; sporadic pituitary adenoma